Gli studi biblici africani nel contesto della teologia decoloniale: tensioni tra ‘centro’ e ‘periferie’ - Tonelli, Debora (B@belonline, 2022)
In recent decades, African biblical studies have acquired ever greater visibility, helping to rethink the theological tradition starting from a decentralized perspective. This triggered a process of reflection on traditional epistemology - theological, but also political and social - and, consequently, favored initiatives and paths aimed at social, political and religious practice emancipation. The epistemic revolution to which African biblical studies contribute, however, does not limit its force of action to the continent, but calls for a different and more inclusive epistemic reflection even in those cultures that historically have been able to impose themselves more outside their own geographical borders. The aim of this essay is to make known and broadly analyze the role of African biblical studies in the horizon of decolonial theology and in the broader and more challenging process of rethinking the polarization between "center" and "peripheries" radicalized by the colonial experience before and then from globalization.